Development of Heat Transfer Correlation for Supercritical Water in Vertical Upward Tubes. Issue 8 (9th May 2019) - Lei, Xianliang; Guo, Yumeng; Zhang, Weiqiang; Li, Huixiong; Li, Liangxing
ABSTRACT: Supercritical water is widely used in many advanced single-phase thermosiphons due to its favorable heat and mass transfer characteristics and potentially high thermal efficiency. However, the heat transfer characteristics of supercritical water in the deterioration regime cannot be accurately predicted due to the absence of exact evaluation of the effect on steep variation in thermophysical properties near the pseudocritical point. The present paper focuses on the deterioration mode by analyzing the physical mechanism and constructing a new correlation. About 3, 000 experimental data on supercritical water, including 40 deteriorated heat transfer cases from open literature, were collected. Quantitative assessment of heat transfer behavior was conducted based on existing test data and previous criteria gathered from extant literature. Based on experimental data evaluation and phenomenological analysis, an improved dimensionless correlation is proposed by introducing multi-dimensionless parameters, which can correct the deviation of heat transfer from its conventional behavior in the Dittus-Boelter equation. Comparisons of various heat transfer correlations with the selected test data show that the new correlation agrees better with the test data versus other correlations selected from the open literature.